Logística inversa: una solución a la disposición de medicamentos en el hogar - Manzolillo, Bartolomé (Gaceta Médica de Caracas, 2021)
La producción y consumo de medicamentos son cada vez más importantes para cubrir el crecimiento de la población mundial y sus necesidades de curar o prevenir enfermedades. Este consumo trae como consecuencias su acumulación en los hogares, por lo que finalmente el paciente los dispone sin hacerlo de forma apropiada, afectando al ambiente y la salud pública. Reverse logistics: A solution for medicines disposition at home The production and consumption of medicines are becoming increasingly important to meet the growth of the world’s population and its needs to cure or prevent diseases. This consumption generates the accumulation in households and eventually, the patient disposes of the medicines in inappropriate ways, which raises concerns about the effects these wastes may have on the environment and public health.